Preliminary screening of active chemical components Found in twelve species of ipomoea l. - SARINI. G; A.K. BOPAIAH (International Journal of Pharma and Bio Sciences, 2018)
Secondary metabolites help in important plant functions and they are specific for each species. The identification of secondary metabolites in the 12 species of Ipomoea may help in analyzing their chemical constituents and correlating them with the external morphology of the plants. Some of the secondary metabolites are being used by humans as medicines, in food as flavouring agents and as drugs. Qualitative analysis was done to test the presence of alkaloids, flavonoids, glycoside, phenol, saponins, tannin, terpenoids, and phlobatannins on the ethanolic leaf extract of 12 species of Ipomoea namely Ipomoea obcura, Ipomoea indica, Ipomoea quamoclit, Ipomoea hederifolia, Ipomoea carnea, Ipomoea cairica, Ipomoea horsfalliae, Ipomoea staphylina, Ipomoea purpurea, Ipomoea muricata, Ipomoea beraviensis and Ipomoea batatus. The present study has revealed the presence of alkaloids, flavonoids and glycosides in all the samples analyzed and the absence of tannins, phenols, saponins, terpenoids and phlobatannins in few samples.